Effect of polyglycolic acid mesh for prevention of pancreatic fistula after pancreatectomy: A systematic review and meta-analysis. Issue 34 (21st August 2020) - Zhang, Wei; Wei, Zhicheng; Che, Xu
Abstract : Abstract: Postoperative pancreatic fistula (POPF) is the most common and intractable complication after partial pancreatectomy, with an incidence of 13% to 64%. Polyglycolic acid (PGA) mesh is a new technique that is designed to prevent POPF, and its effect has been evaluated in several randomized controlled trials and some retrospective cohort studies. In this study, we systematically and comprehensively analyzed the efficacy of PGA mesh based on reported studies. We searched Medline, Embase, and Cochrane Library databases in English between January 2010 and October 2019. Analysis was performed by using Review Manger 5.3 software. Three RCTs and 8 nonrandomized studies were eligible with a total of 1598 patients including 884 PGA group patients and 714 control group patients. For pancreatoduodenectomy (PD), distal pancreatectomy (DP), and the 2 partial pancreatectomy (PD or DP), we found significant statistical differences in overall POPF (relative risk [RR] = 0.75, 95% confidence interval [CI] = 0.61–0.91, P = .004; RR = 0.74, 95% CI = 0.57–0.96, P = .02; RR = 0.76, 95% CI = 0.64–0.89, P = .0009, respectively) and clinical pancreatic fistula (PF) (RR = 0.5, 95% CI = 0.37–0.68, P < .00001; RR = 0.31, 95% CI = 0.21–0.46, P < .00001; RR = 0.41, 95% CI = 0.32–0.52, P < .00001, respectively) in favor of PGA. For partial pancreatectomy, significant statistical differences were found in overall complications (RR = 0.77, 95% CI: 0.67–0.88, P = .0002) and estimated blood loss (weighted mean difference [WMD] = −53.58; 95% CI: −101.20 to −5.97, P = .03) in favor of PGA. We did not find significant differences regarding operative time (WMD = −8.86; 95% CI: −27.59 to 9.87, P = .35) and hospital stay (WMD = −2.73; 95% CI: −7.53 to 2.06, P = .26). This meta-analysis shows the benefits of the PGA mesh technique regarding POPF, clinical PF, and postoperative complications. This still needs to be verified by more randomized control trials. Abstract : Supplemental Digital Content is available in the text